Pengaruh Karakteristik Peserta, Desain, dan Lingkungan Pelatihan Terhadap Peningkatan Kompetensi Peserta Pelatihan Budidaya Lebah Madu CV. Flora Nauli - Novianda, Chichi; Azizah, Siti (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Flora Nauli is one of the farms in Pematang Siantar that provides training in honey bee cultivation. The purpose of this research is to determine the influence of participant characteristics, training design, and training environment on increasing the competency of Flora Nauli honey bee cultivation training participants in Simalungun Regency. The number of respondents in this research was 30 farmers. This research variable includes participant characteristics (X1): age, education level, experience, and business scale indicators, the training design (X2) includes: instructor, materials, and methods, the environment variables (X3) include: physical and non-physical environments, and participants' competency level variables (Y) are measured through participants' cognitive, affective, and psychomotor. Data analysis uses qualitative, quantitative, and multiple linear regression methods, with interviews and questionnaires used for data collection. The results of this research show that participant characteristics, training design, and training environment significantly increase the competency of training participants. Partial participant characteristic variables did not have a significant effect, while design and training environment variables significantly increased participant competency. The participant competency level variable also shows an average score of 3.87, which is a very good category. This research shows that training programs have an important role in improving human resource competence.